Promoting Physics Literacy through Enquiry-based Learning Online - Wan Ng; Elizabeth Angstmann (Seyit Ahmet Kıray, 2017)
In Australia, as in a number of other countries, studies have consistently shown a low enrolment trend towards Physics by students in post-secondary years, due partly to the subject being perceived as conceptually difficult and abstract to grasp. In order to promote Physics literacy, continued opportunities such as online courses for students to engage in Physics education are necessary. For courses that are aimed at reaching out to students with little Physics background, the pedagogy needs to be considered carefully, especially when it is taught entirely in an online learning environment. This research investigated a fully online, inquiry-based course design aimed at motivating students to learn Physics and its impact on students' learning experiences at an Australian university. The research compared the learning experiences of students whose career trajectories are science-related and those who are not in order to assess its effectiveness in promoting Physics literacy. An online survey containing Likert-scale items as well as open questions elicited students' perceptions of the impact of the online course on their learning. The volunteer research participants were 59 undergraduates, where about two thirds of the participants were science students and one-third non-science students. The results showed that students were positive about the pedagogical structure and content in the online Physics course. Except for one item, there were no other statistically significant differences between science and non-science students' responses in the study, suggesting that the pedagogical design catered to the needs of both groups of students, an important element in promoting Physics literacy across a broad range of students.